Breaking a dogma: orthodontic tooth movement alters systemic immunity - Yehuda Klein; Eilon David; Noy Pinto; Yasmin Khoury; Yechezkel Barenholz; Stella Chaushu (SpringerOpen, 2024)
Abstract Background The prevailing paradigm posits orthodontic tooth movement (OTM) as primarily a localized inflammatory process. In this study, we endeavor to elucidate the potential ramifications of mechanical force on systemic immunity, employing a time-dependent approach. Materials and methods A previously described mouse orthodontic model was used. Ni-Ti. springs were set to move the upper 1st-molar in C57BL/6 mice and the amount of OTM was. measured by µCT. Mice were allocated randomly into four experimental groups, each. corresponding to clinical phases of OTM, relative to force application. Terminal blood. samples were collected and a comprehensive blood count test for 7 cell types as well as. proteome profiling of 111 pivotal cytokines and chemokines were conducted. Two controls. groups were included: one comprised non-treated mice and the other mice with inactivated springs. Results Serum immuno-profiling unveiled alterations in cellular immunity, manifesting as. changes in percentages of leukocytes, monocytes, macrophages, neutrophils, and. lymphocytes, alongside key signaling factors in comparison to both control groups. The systemic cellular and molecular alterations triggered by OTM mirrored the dynamics previously described in the local immune response. Conclusions Although the exact interplay between local and systemic immune responses to orthodontic forces require further elucidation, our findings demonstrate a tangible link between the two. Future investigations should aim to correlate these results with human subjects, and strive to delve deeper into the specific mechanisms by which mechanical force modulates the systemic immune response.